Characterization of plasma polymerized HMDSN films deposited by atmospheric plasma jet - Kodaira, F. V.P. [UNESP]; Ricci Castro, A. H. [UNESP]; Prysiazhnyi, V. [UNESP]; Mota, R. P. [UNESP]; Quade, A.; Kostov, K. G. [UNESP] (Elsevier, 2017)
Deposition of plasma polymers using atmospheric pressure plasma jet in mixture of argon, air and hexamethyldisilazane (HMDSN) was studied. The HMDSN monomer, used as film precursor, was carried to the jet nozzle by an auxiliary airflow and mixed with principal argon flow. The films were deposited for different times using mean discharge power of 2.8 W, main argon flow of 1 SLM while the carrier flow (air + HMDSN) was 0.1 SLM. The water contact angles measured across the obtained HMDSN plasma polymer film showed two well-defined areas, one hydrophilic, with contact angle near zero degrees and one hydrophobic, with contact angle around 100 degrees. The FTIR spectra showed that part of the original structure of HMDSN monomer was preserved and new chemical bonds were observed. XPS analysis showed that the deposited coatings are inorganic SiO2-like coatings. The films thickness was evaluated and it reached values about 2 μm in the center and decreased to the border (in continuous deposition mode more rapidly than in the pulsed one). Roughness values were obtained and it is shown that they varied for each region of the film.
Keywords: APPJ; Atmospheric pressure plasma jet; HMDSN; Plasma polymer; Polymeric films